Genomewide Association Analysis of Respiratory Syncytial Virus Infection in Mice - Stark, James M. (American Society for Microbiology (ASM), 2010)
Respiratory syncytial virus (RSV) is the major cause of lower respiratory tract infection in infants, with about half being infected in their first year of life. Yet only 2 to 3% of infants are hospitalized for RSV infection, suggesting that individual susceptibility contributes to disease severity. Previously, we determined that AKR/J (susceptible) mice developed high lung RSV titers and showed delayed weight recovery, whereas C57BL/6J (resistant) mice demonstrated low lung RSV titers and rapid weight recovery. In addition, we have reported that gene-targeted mice lacking the cystic fibrosis transmembrane conductance regulator (Cftr; ATP-binding cassette subfamily C, member 7) are susceptible to RSV infection. For this report, recombinant backcross and F2 progeny derived from C57BL/6J and AKR/J mice were infected with RSV, their lung titers were measured, and quantitative trait locus (QTL) analysis was performed. A major QTL, designated Rsvs1, was identified on proximal mouse chromosome 6 in both recombinant populations. Microarray analysis comparing lung transcripts of the parental strains during infection identified several candidate genes that mapped to the Rsvs1 interval, including Cftr. These findings add to our understanding of individual RSV susceptibility and strongly support a modifier role for CFTR in RSV infection, a significant cause of respiratory morbidity in infants with cystic fibrosis.